PRODUTOS EDUCACIONAIS NA ÁREA DE ENSINO: CONTRIBUIÇÕES DE UM ITINERÁRIO DIDÁTICO-PEDAGÓGICO À LUZ DA ACESSIBILIDADE PEDAGÓGICA - Zuquetto, Suelen da Silva (2021)
The operationalization of the students’ inclusion process, within the Brazilian education system, is still not enough and, in most cases, education professionals do not have an ideal teacher formation nor didactic resources enough for subsiding their teaching proposals. On the other hand, new horizons are opened to filling formation gaps of human and material resources from professional maters’ degree courses related to education that aim continuing education of teachers and parallelly the development of education products corresponding to labor craft. Having these premises, this dissertation aimed to investigate the possibilities of the development of education products (EP) that are pedagogically accessible to the area of teaching in professional post-graduation programs. In this present research, linked to the Graduate Program in the Teaching of Science and Mathematics, of the Franciscan University, and to the research line of Teacher Education in Science and Mathematics, one can highlight the relevance that EPs in teaching, can be based upon a pedagogical and didactic itinerary in the light of pedagogical accessibility. In this dissertation, the EP is presented in the form a digital guidebook, named Itinerary for the Elaboration of Pedagogically Accessible Education Products. To do so, this research is based upon the elaboration criteria of assistive technologies and the Coordination of Superior Level Staff Improvement to the elaboration of EPs, upon the construction processes of accessible EPs, upon the studies of Universal Design for Learning (UDL) and, especially, upon the contributions of neuroscience for learning. Regarding the methodology, of a qualitative nature and documental and bibliographical feature, the elected method was the exploratory and descriptive. The EP trial phase was operationalized along with the students of the Professional Masters’ Degree Course from the Graduate Program in the Teaching of Science and Mathematics, of the Franciscan University, in the discipline of Sciences at Early Basic Education: Contents and Production of Activities. Thus, it was possible to verify the didactic and pedagogical functionality of the proposed itinerary in the present EP. One can ratify that an EP construction that is pedagogically accessible runs through actions that need to be tracked, identified, and discussed based on scientific findings. Therefore, the proposed itinerary to this EP contributes as a didactic and pedagogical guide and offers a greater objectivity to the development of a pedagogical artifact, observing the accessibility perspective. Thus, the Itinerary for the Elaboration of Pedagogically Accessible EPs presents conditions for optimization and subsidies for the development of the EP, assessing the aspects of inclusion in professional programs of postgraduation or in other convenient spaces.